Biomimetic earthworm dynamic soil looser for improving soybean emergence rate in cold and arid regions - Zhao, Jiale; Wang, Xiaogeng; Lu, Yun; Wei, Yanpeng; Guo, Mingzhuo; Fu, Jun (International Journal of Agricultural and Biological Engineering, 2021)
In cold and arid regions, soil moisture content and accumulated temperature were seriously insufficient during spring sowing, which made it difficult for soybean seedling to emerge. Based on the principle of earthworm optimization and improvement of soil structure, this study innovatively designed a biomimetic earthworm dynamic soil looser through bionic design and theoretical calculation. By highly reducing the movement path and mode of earthworm in the soil, the mechanism could improve the soil temperature (ST) and soil moisture content (SMC), and thus greatly improve the soybean emergence rate (SER). In this study, the effects of biomimetic earthworm dynamic soil looser and its design parameters on soil temperature (ST), soil moisture content (SMC) and soybean emergence rate (SER) were investigated by two-factor test, analysis of variance (ANOVA) and Least significant Difference (LSD). Regression analysis was used to establish the mathematical model between design parameters and soybean emergence rate. MATLAB software was used to optimize the model, and the optimal design parameter combination was obtained. The contrast experiments showed that the biomimetic earthworm dynamic soil looser could construct the soil structure more suitable for the cold and arid regions. Compared with rotary blade (RB) and notched disc harrow (DH), biomimetic earthworm dynamic soil looser could increase soil moisture content by 41.30% and 27.50%, respectively. Compared with the notched disc harrow, the soil temperature could be increased by 7.97%. There was no significant difference between the effect of rotary blade on soil temperature (p>0.05). The soybean emergence rate was increased by 25.40% and 20.70%, respectively, compared with that of notched disc harrow and rotary blade. Keywords: bionics, earthworm, tillage, soil temperature, soil moisture content, soybean emergence rate DOI: 10.25165/j.ijabe.20211403.6326 Citation: Zhao J L, Wang X G, Lu Y, Wei Y P, Guo M Z, Fu J. Biomimetic earthworm dynamic soil looser for improving soybean emergence rate in cold and arid regions. Int J Agric & Biol Eng, 2021; 14(3): 22–31.